2018
DOI: 10.1016/j.jvb.2017.12.004
|View full text |Cite
|
Sign up to set email alerts
|

The short form of the Workplace Affective Commitment Multidimensional Questionnaire (WACMQ-S): A bifactor-ESEM approach among healthcare professionals

Abstract: Although it has long been recognized that employees' workplace affective commitment can be directed at a variety of foci, theory and research on this multifocal perspective remain underdeveloped, possibly due to the lack of a short, yet comprehensive measure. The purpose of the present study was to assess the psychometric properties of a newly developed short (24-item) version of the Workplace Affective Commitment Multidimensional Questionnaire (WACMQ-S), covering affective commitment directed at the organizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
83
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(96 citation statements)
references
References 110 publications
7
83
0
1
Order By: Relevance
“…affective) with ACS, ACO reflects different foci and these two forms of attachment do constitute two different constructs with different effects (Vandenberghe & Bentein, 2009). Indeed, recent research showed workplace affective commitment to have a complex multifocal structure and supported the importance of considering specific affective commitment foci separately for they have unique relations with health care workers' attitudes and behaviours, beyond their global levels of general worklife affective commitment (Perreira et al, 2018).…”
Section: Indirect Effectsmentioning
confidence: 98%
“…affective) with ACS, ACO reflects different foci and these two forms of attachment do constitute two different constructs with different effects (Vandenberghe & Bentein, 2009). Indeed, recent research showed workplace affective commitment to have a complex multifocal structure and supported the importance of considering specific affective commitment foci separately for they have unique relations with health care workers' attitudes and behaviours, beyond their global levels of general worklife affective commitment (Perreira et al, 2018).…”
Section: Indirect Effectsmentioning
confidence: 98%
“…[98]. AC, and organizational citizenship demonstrates work commitment [85]. Moreover, [75] found that identification and internalization are positively linked to AC, while [6] indicated that career motivation and AC have a positive relationship.…”
Section: A Affective Commitmentmentioning
confidence: 97%
“…Finally, Table 5 and Figure 2 shows results of the hypotheses tests and the final structural model, respectively. In order to estimate the structural model, a bootstrapping procedure with 5,000 resamples was conducted to generate the t-values, based on the method of [85]. As shown in Figure 2 and Table 5,…”
Section: A Measurement Model and Structural Model Estimationmentioning
confidence: 99%
“…Affective commitment, which denotes an emotional attachment, develops when customers have a high level of involvement and participation in an organisation (Long, Yong & Chuen, 2016). Furthermore, affective commitment increases the likelihood of customers to engage in behaviour that seeks to increase organisational performance and extend beyond the role of customer expectations (Perreira & Berta, 2016).…”
Section: Commitmentmentioning
confidence: 99%